PENGARUH STRUKTUR CORPORATE GOVERNANCE, AUDIT TENURE DAN UKURAN KANTOR AKUNTAN PUBLIK (KAP) TERHADAP INTEGRITAS LAPORAN KEUANGAN - Qoyyimah, Sofia Dinil; Kholmi, Masiyah; Harventy, Gina (Universitas Muhammadiyah Malang)
Purpose of this research to know influence of corporate governance, audit tenure, and KAP size tointegrity of financial statement. The method of analysis used is logistic regression analysis. Theresearch sample consisted of 14 state-owned companies listed in BEI 2011-2014.the results ofthe study show that the integrity of financial statements can not be controlled with corporategovernance, audit tenure and KAP size.Keywords:audit tenure, corporate governance, financial statement, KAP size